Reformulation of dairy cow diets based on rumen degradable protein and total digestible nutrient with varying levels on in vitro fermentability and digestibility. Issue 1 (November 2021) - Sahroni, W P; Permana, I G; Despal,
Abstract: Rumen degradable protein (RDP) needs to be balanced with the adequacy of rumen undegradable protein (RUP) and energy for optimal microbial growth. Therefore, this study aimed to determine the optimal level of the RDP:RUP ratio and the energy level of dairy cattle rations using the in vitro method. The rumen inoculum used to carry out this research, was obtained from two bull rumen fistulated of Friesian Holstein. The treatments consisted of 3 levels of RDP:RUP ratio, namely 50:50, 55:45 and 60:40, while the energy levels consisted of total digestible nutrient (TDN) levels of 65.6% and 68.6%. The experimental design was a factorial randomized block, while data were analyzed using ANOVA and Duncan multi range's test. The result showed the ratio of RDP:RUP had an effect on DMD, OMD, NH3, and rumen microbe. Furthermore, the higher TDN content increased significantly DMD, OMD, total VFA, and partial VFA. The increase in the microbial population was associated with a rise in total VFA and NH3 concentrations. This research concluded, the rations with RDP:RUP (60:40) ratio increased the population of bacteria and protozoa, while the availability of ammonia in the rumen, and the high level of TDN provided a higher supply of VFA, DMD, and OMD.